2003
DOI: 10.1016/s0014-5793(03)00807-x
|View full text |Cite
|
Sign up to set email alerts
|

S‐nitrosation of Cys‐800 of HIF‐1α protein activates its interaction with p300 and stimulates its transcriptional activity

Abstract: Hypoxia inducible factor 1 (HIF-1) is a heterodimeric transcriptional complex that plays pivotal role in the regulation of cellular utilization of oxygen as well as glucose and is an essential regulator of angiogenesis in solid tumor and ischemic disorders. Recently HIF-1K K, a subunit of HIF-1 complex, was characterized as a potential target for S-nitrosation, providing no information about the impact of this posttranslational modi¢cation on the protein transactivation. Cys-800 of HIF-1K K protein has reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(112 citation statements)
references
References 28 publications
(30 reference statements)
3
105
1
3
Order By: Relevance
“…This was postulated to occur via enhancement of the interaction between the CAD and CBP/p300, thus linking cellular redox status to recruitment of CBP to HIF. 56 However, more recent quantitative interaction studies with purified proteins and peptides demonstrated a significant decrease in p300 binding upon Cys800 S-nitrosylation. 41 SUMOylation of HIF-1a has also been described by several groups, however the reported outcomes of this modification are varied.…”
Section: Other Modifications Affecting Hif-driven Transcriptionmentioning
confidence: 99%
“…This was postulated to occur via enhancement of the interaction between the CAD and CBP/p300, thus linking cellular redox status to recruitment of CBP to HIF. 56 However, more recent quantitative interaction studies with purified proteins and peptides demonstrated a significant decrease in p300 binding upon Cys800 S-nitrosylation. 41 SUMOylation of HIF-1a has also been described by several groups, however the reported outcomes of this modification are varied.…”
Section: Other Modifications Affecting Hif-driven Transcriptionmentioning
confidence: 99%
“…Hypoxia-inducible factor (HIF)1α also is regulated in a redox dependent manner, and its degradation and activation are regulated via cysteine oxidation. S-nitrosylation of HIF1α promotes its stabilization [205], and S-nitrosylation of Cys-800 activates HIF1α-p300 interaction and stimulates protein transactivation [206].…”
Section: Redox Regulation Of Transcription Factorsmentioning
confidence: 99%
“…Additionally, nitric oxide (NO) signaling induces covalent modification of HIF-1 protein. NO stimulates S-nitrosation of cysteine 800, a critical residue within the C-TAD of HIF-1α, which enhances interaction of HIF-1 with p300/CBP and increases HIF-1 activity [42,43].…”
Section: Regulation Of Gene Expression Through Covalent Modification mentioning
confidence: 99%